A influência da adição de Bi2O3 nas propriedades dielétricas em micro-ondas da matriz BiCuTi3FeO12 (BCTFO) - Colares, Diego da Mota (2020)
In this dissertation, the behavior of the addition of bismuth oxide (Bi2O3) on the BiCuTi3FeO12 ceramic matrix (BCTFO) was analyzed for application in dielectric resonant antennas (DRAs) in the microwave range. For this, composites were produced with the addition of Bi2O3 in the BCTFO matrix whose percentages varied from 0%, 20%, 60% and 80%. In order to confirm and study the crystalline structures of the BCTFO and Bi2O3 phases in the samples, X-ray diffractions were made. To characterize the microwave dielectric properties of these composites, first, the temperature coefficient of the resonance frequency (τf) was analyzed in each of the composites using the Silva-Fernandes-Sombra (SFS) method. As a result, such measures indicated thermal stability with increased Bi2O3 addition over the BCTFO ceramic matrix, as the τf varied from 1683 ppmºC-1 to 129 ppmºC-1 . Secondly, impedance measurements were made in the microwave range. Thus, the impedance measures indicated that the composites previously mentioned have resonant frequencies from 2.42 GHz to 3.65 GHz. In addition, the impedance measures also indicated a reduction in the relative permissiveness in relation to the percentage increase of Bi2O3 in the samples, because the relative permittivity varied from 71 to 21. Return losses were also obtained by means of impedance measurements in all samples and these showed less than -10 dB. In addition to the experimental measurements, computer simulations were used using the HFSS program in order to validate the data obtained experimentally and to obtain composite antenna parameters, such as: radiation diagram, directivity, gain and efficiency. Thus, all analyzed composites have good antenna parameters and can be applied as DRAs, since the efficiencies of all manufactured DRAs are above 50%.